2004
DOI: 10.1007/s10517-005-0073-0
|View full text |Cite
|
Sign up to set email alerts
|

Neutron flow exposure as a test for survival of Artemia Salina spores

Abstract: Live and heat-inactivated Artemia salina spores (samples with the same mass and filling density) were exposed to a flow of thermal neutrons from a (252)Cf radioactive source at an equivalent dose power of about 1 microSv/h. Irradiation led to a 4-fold acceleration of nauplius development and to modification of the element profiles of live spores. The difference between absorption/diffusion of thermal neutrons by live and dead spores was revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…According to our data, the specific change in element profiles of A. salina cysts followed by a biological response also appears after other physical action. Particularly, with a monthly cold (−20°S) activation of cyst germination, the copper-zinc ratio significantly changes equimolar, and at the same time, values for the rest of the elements stay unchanged [6][7][8][9][10][11][12][13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our data, the specific change in element profiles of A. salina cysts followed by a biological response also appears after other physical action. Particularly, with a monthly cold (−20°S) activation of cyst germination, the copper-zinc ratio significantly changes equimolar, and at the same time, values for the rest of the elements stay unchanged [6][7][8][9][10][11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…The peculiarity of this decrease was the presence of a kinetic failure lasting 1–3 minutes. The indicated kinetic failure degenerated when dinitrophenol (DNP), the uncoupler of oxidative phosphorylation process, was introduced into the medium, which leads, as is known [ 11 ], to the discharge of transmembrane electrochemical potential (see Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…our previous experiments with resting eggs of brine shrimp (Artemia salina) [6]. The shape of these dependences probably depends on the number and composition of species in the biocenosis.…”
Section: Bulletin Of Experimental Biology and Medicine Vol 143 Nomentioning
confidence: 88%
“…Moreover, it increases by many times during solar flares. Previous studies revealed the existence of strong biological responses to ultraweak fluxes of thermal neutrons (V. V. Lednev et al) [1,6,11]. These data suggest that thermal neutrons has a function of messengers, which allows the perception of astrogeophysical events by living organisms.…”
mentioning
confidence: 85%
See 1 more Smart Citation